A bimodal accessibility analysis of Australia through application programming interfaces. Issue 3 (1st January 2020) - Meire, Sarah; Derudder, Ben
ABSTRACT: In this paper we discuss some of the major strengths and limitations of an application programming interfaces (API)-based approach to studying accessibility in transport networks. To this end, we present a framework for assessing the bimodal accessibility of locations by using publicly available web-based resources that can be accessed via APIs. By way of empirical example, we query the Google Maps Distance Matrix and Google QPX Express APIs to collect travel time for both land- and airside travel, and process the extracted data using Python. We then apply our analytical strategy to the case of Australian statistical units to illustrate our data collection and processing framework, and in the process try to improve our understanding of the Australian urban-geographical landscape in terms of its bimodal accessibility. In addition to a largely-expected accessibility pattern centred on major agglomerations, we also reveal a number of idiosyncratic and perhaps less-expected geographical patterns.